Drug-resistant strains of Mycobacterium tuberculosis: cell envelope profiles and interactions with the host - Schami, Alyssa; Islam, M. Nurul; Belisle, John T.; Torrelles, Jordi B. (Frontiers in Cellular and Infection Microbiology, 2023)
In the past few decades, drug-resistant (DR) strains of Mycobacterium tuberculosis (M.tb), the causative agent of tuberculosis (TB), have become increasingly prevalent and pose a threat to worldwide public health. These strains range from multi (MDR) to extensively (XDR) drug-resistant, making them very difficult to treat. Further, the current and future impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the development of DR-TB is still unknown. Although exhaustive studies have been conducted depicting the uniqueness of the M.tb cell envelope, little is known about how its composition changes in relation to drug resistance acquisition. This knowledge is critical to understanding the capacity of DR-M.tb strains to resist anti-TB drugs, and to inform us on the future design of anti-TB drugs to combat these difficult-to-treat strains. In this review, we discuss the complexities of the M.tb cell envelope along with recent studies investigating how M.tb structurally and biochemically changes in relation to drug resistance. Further, we will describe what is currently known about the influence of M.tb drug resistance on infection outcomes, focusing on its impact on fitness, persister-bacteria, and subclinical TB.